The functions and mechanisms of sequence differences of DGAT1 gene on milk fat synthesis between dairy cow and buffalo. Issue 2 (May 2020) - Bhattarai, Dinesh; Dad, Rahim; Worku, Tesfay; Xu, Sutong; Ullah, Farman; Zhang, Min; Liang, Xianwei; Den, Tingxian; Fan, Mingxia; Zhang, Shujun
Abstract: In this research communication we describe the DGAT1 sequence and promoter region in dairy cows and buffalo and compare the activities of DGAT1 between the two species in order to increase knowledge of the cause of milk fat variation. pGL-3 basic vectors were used to construct the reporter gene. Based on the predicted promoter region, 4 truncated plasmid vectors were constructed in cow-DGAT1 and 3 plasmid vectors in buffalo-DGAT1. Each reporter plasmid was transfected into the bovine mammary epithelial cell (BMEC), 293T cell, and CHO cells to analyze the activity using Dual-Luciferase Reporter Assay System. The results show that the region between −93 to −556 bp was essential for cow promoter activity while −84 to −590 bp was essential for buffalo promoter activity revealing these regions contain core promoter. The buffalo has higher promoter activity than cow yet it was not statistically significant. Comparison of candidate mutation K232A between cow and buffalo population revealed the presence of both the allelic population in dairy cows (lysine and alanine) however, only K (lysine) allelic amino acid was found in buffalo population. The absence of the alanine allelic population from buffalo explains the higher fat content of buffalo milk.